A new species of Bent-toed Gecko (Squamata, Gekkonidae, Cyrtodactylus) from the Shan Plateau in eastern Myanmar (Burma) - Grismer, L. Lee; Wood, Perry L. Jr.; Quah, Evan S. H.; Thura, Myint Kyaw; Oaks, Jamie R.; Lin, Aung (Zootaxa, 2019)
An integrative taxonomic analysis of the Cyrtodactylus linnwayensis group of the Shan Plateau recovered two new populations from isolated karst habitats near Pinlaung Town, Shan State as a new species, C. pinlaungensis sp. nov. Cyrtodactylus pinlaungensis sp. nov. is most closely related to a clade comprising C. linnwayensis and C. ywanganensis from the western edge of the Shan Plateau approximately 90 km to the northwest. Cyrtodactylus pinlaungensis sp. nov. can be distinguished from all members of the C. linnwayensis group by a number of statistically different morphological characters, discrete color pattern differences, and its heavy tuberculation. It also bears an uncorrected pairwise sequence divergence of 5.0–7.6% from all other species combined based on the mitochondrial gene ND2 and its flanking tRNAs. The discovery of this new species on the Shan Plateau continues to underscore the fact that this region is rapidly emerging as a herpetological diversity hot-spot for Myanmar.